The Role of Growth Factors (VEGF, TGF-β1) and Cyclic Guanosine Monophosphate in the Formation of Pulmonary Hypertension in Children with Bronchopulmonary Dysplasia - A.S. Senatorova; O.L. Logvinova (Zaslavsky O.Yu., 2013)
In 82 children with bronchopulmonary dysplasia (from 1 to 36 months of corrected age) we investigated the level of VEGF, TGF-β1 in blood and cyclic guanosine monophosphate (cGMP) in sputum. It was revealed that children with bronchopulmonary dysplasia had a significant increase in TGF-β1 (p < 0.05) and cGMP (p < 0.01-0.001), reduced VEGF (p < 0.05), indicating inhibition of angiogenesis, activation of fibrosis factors and endothelium-dependent vasodilation. Reliable direct dependence of activation of TGF-β1 in blood and cGMP in sputum, as well as inverse correlation between VEGF in blood and rLA had been proved, which gave reason to think of pulmonary hypertension as an adverse factor in fibrosis activation and angiogenesis inhibition in children with bronchopulmonary dysplasia. Reduced oxygen saturation and oxygen partial pressure moderately activated cGMP, but did not provide a sufficient reduction of pressure in the pulmonary artery.